Impact of Artificial Intelligence towards customer relationship in Indian banking industry - Kumar, Jitendar; Gupta, Dr. Sudipta Sen (Gyan Management Journal, 2023)
The most significant & ground-breaking innovations in the banking  industry is the growing emphasis on the needs of the consumer.  Consumers that are technically knowledgeable and regularly interact  with cutting-edge innovations want banks to provide smooth  experiences. For operations like digital money, e-banking, and real  cash transfers, financial institutions have extended their industrial  landscape to include retail, IT, and telecom in order to meet these  requirements. While these developments have made it possible for  consumers to reach the majority of banking services at anytime,  anywhere, they have also come at a cost to the financial sector.  This study also sheds light on the advantages and disadvantages of  adopting AI technology in the Indian banking sector. This study is of  descriptive nature which describes the usage of artificial intelligence  in banking services and the effect on relationship with customer. Data  was collected from total 187 customers of Delhi of public and private  sector banks using Questionnaire.
Keywords: Artificial Intelligence; Relationship marketing; Banking Industry; Customer relationship